PESANTREN SEBAGAI BENTENG PERADABAN ISLAM INDONESIA - H.B. Fananie, T. S. Purnama (Fakultas Agama Islam, Universitas Mathla'ul Anwar, 2023)
The reason for the existence of pesantren is to transmit the products of traditional Islamic scholastic thought. This means that pesantren are genealogically tied to the culture and traditions of medieval Islamic thought. When the fortress of civilization of Islamic countries was in ruins, Indonesia still had the guardians of the fortress of civilization. They are scholars, students, Islamic boarding schools, madrasas, taklim assemblies, as well as organizations concerned with Islam. This article shows that the existence of pesantren as educational institutions shows the basis of Indonesian Islamic civilization.